Investigation of Cajuput and Lemongrass Essential Oils Supplemented in Alcohol-Free Mouthwash: Anti-Inflammation on Human Gingival Fibroblast Cells In Vitro - Reungsuwat, Sirirat; Sookkhee, Siriwoot; Itthidecharon, Chintana; Wanachantararak, Phenphichar (Trends in Sciences, 2023)
Alcohol-free mouthwash containing essential oils is a helpful adjunct to self-performed oral hygiene of patients with periodontal disease due to its antimicrobial and anti-inflammatory properties. This study aimed to investigate the anti-inflammatory activity of cajuput and lemongrass essential oils supplemented in alcohol-free mouthwash on human gingival fibroblast cells and RAW 264.7 macrophages, which were incubated in a complete medium. In the current in vitro study, 3 types of mouthwash, including 12 % (v/v) alcohol-free mouthwash, 0.8 % (v/v) cajuput essential oil and 0.4 % (v/v) lemongrass essential oil supplemented in alcohol-free mouthwash, and 0.12 % chlorhexidine mouthwash, were evaluated. All 3 types were determined for cytotoxicity by MTT assay. The sub-IC50 concentration of each mouthwash was calculated to investigate anti-inflammatory activities via the inhibition of lipopolysaccharide-activated nitric oxide production, cyclooxygenases-2, interleukin-1β and interleukin-6 gene expression. The wound healing rate was determined by scratch assay. The results demonstrated that the sub-IC50 concentrations of essential oils in 0.8 % (v/v) cajuput essential oil and 0.4 % (v/v) lemongrass essential oil supplemented in alcohol-free mouthwash significantly inhibited nitric oxide production in lipopolysaccharide-activated RAW 264.7 macrophages and reduced the gene expression of cyclooxygenases-2, interleukin-1β and interleukin-6 in lipopolysaccharide-activated human gingival fibroblast cells, while stimulating the migration of human gingival fibroblast cells, similar to the sub-IC50 concentration of 0.12 % chlorhexidine mouthwash. These findings suggested that essential oils contained in this mouthwash formula exhibited an anti-inflammatory effect and promoted oral wound healing, which might be used as an alternative agent for patients with periodontal disease. HIGHLIGHTS Cajuput and lemongrass essential oils supplemented in alcohol-free mouthwash expressed anti-inflammatory activity by inhibiting nitric oxide production in LPS-activated RAW 264.7 macrophages and reducing COX-2, IL-6 and IL-1β expression in LPS-activated HGFs, as well as by promoting oral wound healing, similar to chlorhexidine mouthwash, which is a common, well-known agent in dental treatment Our findings suggested that this novel mouthwash may be an alternative agent in preventing oral inflammatory diseases, especially periodontal disease GRAPHICAL ABSTRACT